Synthesis and Antimicrobial Activity of Ethyl-2-chloro-4-substituted 6-(4-Methoxybenzoyl)-4H-thieno[3,2-b]pyrrole-5-carboxylates - Ashok, D.; Satish Goud, P.; Shravani, D.; Rajaiah, J.; Sarasija, M. (Asian Journal of Chemistry, 2011)
Ethyl-2-chloro-6-(4-methoxybenzoyl)-4H-thieno[2,3-b]pyrrole-5-carboxylate (3) has been prepared by refluxing a mixture of 2-chlorothieno[2,3-b]pyrrole-5-carboxylate, 4-methoxy benzoylchloride and TiCl4 in dichloromethane. Ethyl-2-chloro-4-substituted 6-(4- methoxybenzoyl)-4H-thieno[3,2-b]pyrrole-5-carboxylates (4a-e) were synthesized in good yields by treating 3 with ethyl chloroformate at cold conditions in presence of 60 % sodium hydride in DMF. All the compounds synthesized were characterized on the basis of their IR, 1H NMR and mass spectral data and screened for their antimicrobial activity.